The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.5935/1806-6690.20160029
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variability of the physical attributes of soil under pasture

Abstract: RESUMO -O objetivo desse trabalho foi avaliar a variabilidade espacial de atributos físicos do solo para áreas de Latossolo, Argissolo e Cambissolo ocupadas por pastagens. O conhecimento dessa variabilidade é importante, pois ela influencia a qualidade das pastagens e a recarga de água subterrânea. Foram coletadas 154 amostras georreferenciadas para cada área de estudo. Para analisar os dados foi usada a estatística descritiva e a geoestatística. A dependência espacial ocorreu para a maioria dos atributos físi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
4
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 18 publications
4
4
0
1
Order By: Relevance
“…The TP and K 0 decreased as PR and BD increased (Figures 2, 3, 4, and 5), the results similar to findings of Guimarães et al (2016). According to Mion et al (2012), TP shows a strong correlation with PR, which tends to increase as TP is reduced.…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations
“…The TP and K 0 decreased as PR and BD increased (Figures 2, 3, 4, and 5), the results similar to findings of Guimarães et al (2016). According to Mion et al (2012), TP shows a strong correlation with PR, which tends to increase as TP is reduced.…”
Section: Resultssupporting
confidence: 80%
“…The PR for 0.0 -0.1 m showed high variability, as also reported by Mion et al (2012), who analyzed the spatial variability of the physical attributes in a yellow argisol under alternate sheep grazing; those authors attributed their results to high variability of the average, showing a distribution with high heterogeneity of data. After grazing, BD and TP had low variability for all depths sampled, which was also found by Guimarães, Junior, Marques, Santos, and Fernandes (2016), who evaluated the spatial variability of soil physical attributes in latosol, argisol, and cambisol pastures and reported that their results were due to bovines having preferred spots in a pasture, which can promote greater soil heterogeneity. The PR, GM, and K 0 showed moderate variability (Table 3).…”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…Similar fits were found by Resende et al (2014) for clay, silt, and total sand in a Typic Hapludults, by Sana et al (2014) for clay in a Typic Hapludox, and by Guimarães et al (2016) for Ma, TPV, and BD in an Oxisol.…”
Section: Results and Discusionsupporting
confidence: 79%